Advances in pharmacology. - August, J. Thomas (Academic Press, 1995)
Volume 32 contains issues of interest to scientists working in pharmacology, biochemistry, and physiology, particularly to those in HIV, cancer, neurology, and cardio-vascular research and medicine. The chapters on new approaches to cancer therapy and schizophrenia will be of special interest to pharmacologists. Each volume of Advances in Pharmacology provides a rich collection of reviews on timely topics. Emphasis is placed on the molecular bases of drug action, both applied and experimental.